2006
DOI: 10.1590/s0004-282x2006000500012
|View full text |Cite
|
Sign up to set email alerts
|

C1 lateral mass screws for posterior segmental stabilization of the upper cervical spine and a new method of three-point rigid fixation of the C1-C2 complex

Abstract: -Objective: To describe our experience with C1 lateral mass screws as part of a construct for C1-2 stabilization and report an alternate method of C1-C2 complex three-point fixation. Method: All patients that had at least one screw placed in the lateral mass of C1 as part of a construct for stabilization of the C1-C2 complex entered this study. In selected patients who had a higher chance of nonunion an alternate construct was used: transarticular C1-C2 screws combined with C1 lateral mass screws. Results: Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Case reports were excluded and a given series had to report on at least 10 patients to be included. Articles that included posterior cervical instrumentation and fusion at subaxial or occipital levels were included only if the data on patients undergoing C1-2 fusions were separated or those studies specifically describing the consequences of C2 nerve section or preservation for the insertion of C1 lateral mass screws (4,12,32,47). The data from these four studies were used only for the dependent variable outcomes of vertebral artery injury from C1 screw insertion, screw malpositioning, and C2 nerve outcomes.…”
Section: Article Selectionmentioning
confidence: 99%
“…Case reports were excluded and a given series had to report on at least 10 patients to be included. Articles that included posterior cervical instrumentation and fusion at subaxial or occipital levels were included only if the data on patients undergoing C1-2 fusions were separated or those studies specifically describing the consequences of C2 nerve section or preservation for the insertion of C1 lateral mass screws (4,12,32,47). The data from these four studies were used only for the dependent variable outcomes of vertebral artery injury from C1 screw insertion, screw malpositioning, and C2 nerve outcomes.…”
Section: Article Selectionmentioning
confidence: 99%
“…[12] Instability at the atlas and axis requires internal fixation not only for immediate stability, but also to provide long-term immobility so as to attain a solid fusion. [13] There are a wide variety of surgical techniques to achieve this, including anterior odontoid screw fixation or posterior fusion methods such as Gallie-type fusion, BrookeJenkins technique, interlaminar clamps or Sonntag's modified Gallie fusion. [14] Previously wiring methods like sublaminar, spinous process, tension band, facet and triple wiring were done.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 3 studies [13][14][15] have assessed the accuracy of C1 and C2 screw insertion, using postoperative CT scans. Stulik et al 13 reported in a retrospective study that all 56 C1 lateral mass screws (100%) were positioned correctly and only 3 of 56 screws (5.4%) placed into C2 were malpositioned.…”
Section: Discussionmentioning
confidence: 99%